2016
DOI: 10.1016/j.arth.2015.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation and Debridement Before a 2-Stage Revision Total Knee Arthroplasty Does Not Increase Risk of Failure

Abstract: Background Studies have suggested that the success of two-stage revision total knee arthroplasty (rTKA) may be compromised by a prior failed irrigation and debridement (I&D). The purpose of this study was to use two large state inpatient databases to compare the two-stage rTKA failure rates for those patients with and without a prior I&D. Methods This retrospective, longitudinal study used inpatient discharge data from the State Inpatient Database (SID) of two states (California and New York) from 2005 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Management of prosthetic infections should be customised for each patient and usually includes one of 3 main types of surgical interventions [29,84]. First, prosthetic retention with debridement of all infected tissue and irrigation, which is a choice for early postoperative or late haematogenous infections with retention of the prosthesis and long term antibiotic treatment [85,86]. Second, prosthetic exchange, the most frequently used, by one stage or two stage revision.…”
Section: Treatmentmentioning
confidence: 99%
“…Management of prosthetic infections should be customised for each patient and usually includes one of 3 main types of surgical interventions [29,84]. First, prosthetic retention with debridement of all infected tissue and irrigation, which is a choice for early postoperative or late haematogenous infections with retention of the prosthesis and long term antibiotic treatment [85,86]. Second, prosthetic exchange, the most frequently used, by one stage or two stage revision.…”
Section: Treatmentmentioning
confidence: 99%
“…11 It has been demonstrated that treatment of an acute PJI with I&D as the initial treatment does not compromise the subsequent two-stage procedure if this initial treatment modality fails. 12 The surgical decision process can be complex and surgeons take multiple factors into consideration such as the acuity of the infection, virulence of the organism, and variety of patient-related factors when formulating a treatment plan.…”
mentioning
confidence: 99%
“…Another treatment alternative is to proceed to implant removal. Although the real impact of previous failed DAIR on the likelihood of success after exchange surgery is not yet fully understood, most surgeons would agree that exchange surgery is the natural choice when facing a late infection relapse 3 , 4 , 91 . The same might be true in some cases of early failure, especially if significant risk factors for DAIR failure are present (e.g.…”
Section: Failure and Treatment Optionsmentioning
confidence: 99%